2021
DOI: 10.11591/ijece.v11i4.pp3459-3469
|View full text |Cite
|
Sign up to set email alerts
|

Audio compression using transforms and high order entropy encoding

Abstract: <span>Digital audio is required to transmit large sizes of audio information through the most common communication systems; in turn this leads to more challenges in both storage and archieving. In this paper, an efficient audio compressive scheme is proposed, it depends on combined transform coding scheme; it is consist of i) bi-orthogonal (tab 9/7) wavelet transform to decompose the audio signal into low &amp; multi high sub-bands, ii) then the produced sub-bands passed through DCT to de-correlate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The results presented in table below showed that the compression technique in [25] achieved better results for the selected sample.…”
Section: Fig3 -Encoding Unitmentioning
confidence: 88%
See 2 more Smart Citations
“…The results presented in table below showed that the compression technique in [25] achieved better results for the selected sample.…”
Section: Fig3 -Encoding Unitmentioning
confidence: 88%
“…Zainab and et al presents a technique depends on combine transforms (wavelet transform and DCT) coding scheme, to decompose the signal into low and multi high sub bands, bi-orthogonal (tab 9/7) wavelet transform was used then DCT was used to de-correlate the sub-bands then quantization (progressive hierarchical) applied followed by Run Length Encoding and finally LZW was applied to generate the compressed stream [25].…”
Section: Discrete Wavelet Transforms (Dwt)mentioning
confidence: 99%
See 1 more Smart Citation
“…A group of consecutive data is quantized to a data group of discrete values. The primary purpose is to reduce the amount of data in threshold coefficients [8].…”
Section: Quantizationmentioning
confidence: 99%
“…Consequently, we can achieve high compression ratios with acceptable SNR. The resulting signal comparison is done with the SNR, the NRMSE, and the signal-tonoise ratio (PSNR) [12,13]. Smita et al, have applied various speech compression techniques, where the signal is converted to a compressed or compressed form.…”
Section: Literature Reviewmentioning
confidence: 99%